The Intergenerational Distribution of Demographic Fluctuations in Unfunded and Funded Pension Systems - Markus Knell (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
In this paper I use a multi-period OLG model to study how a demographic shock is distributed among different generations. In particular, I investigate whether a funded pension system allows for a smoother adjustment than an unfunded system. The results suggest that the answer to this question depends on the specific organization of the funded system. If the contributions are only invested into a non-accumulated asset in fixed supply (e.g. into "land") and if the investment decisions are guided by fixed rules then the intergenerational distribution of the demographic shock is almost identical in the two systems. Assuming optimal investment decisions, on the other hand, will increase or decrease the fluctuations of the funded pillar (depending on the degree of risk aversion). It is only for the case where all savings are invested into accumulable, productive capital that the funded system will dampen the distributional consequences of a demographic shock.
Keywords: H55; J11; J26; 330